Sustainability communication among accredited hospitals in Türkiye: A website-based ESG content analysis - Yonca Özatkan; Perihan Şenel Tekin (Journal of International Health Sciences and Management, 2026)
Sustainability has become an important healthcare management issue because it is closely related to quality, organizational accountability, efficient resource use, and the long-term continuity of healthcare services. However, little is known about how accredited hospitals communicate sustainability to stakeholders. This study aimed to identify sustainability-related themes presented on the official websites of accredited hospitals in Türkiye and to assess the extent to which these themes reflect integrated institutional communication. A descriptive cross-sectional website content analysis was conducted. The official websites of 56 accredited hospitals, including 39 accredited by Joint Commission International and 17 accredited by the Turkish Healthcare Quality and Accreditation Institute, were systematically reviewed between 1 and 20 April 2026. Publicly available content was coded using predefined environmental, social, and governance indicators. Sustainability communication was most visible in the social dimension, particularly in relation to patients, employees, health and safety, and stakeholder engagement. Governance-related communication was strongest for accreditation and certification, whereas information on organizational structures was less consistent. Environmental topics were less visible overall, and sustainable procurement, transport, food systems, climate change, and carbon-related practices were rarely communicated. Differences between accreditation groups were observed for selected indicators, but these findings reflect variations in public disclosure rather than institutional performance. Overall, sustainability communication remained uneven and largely operational rather than strategically integrated. The study provides a national reference point for understanding how accredited hospitals position sustainability within quality, governance, and accreditation.